TECHNOLOGICAL ASSURANCE OF THE MILLING PROCESS OF PRISMATIC CHANNELS IN HEAT EXCHANGE ALUMINUM ALLOYS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
When milling prismatic grooves in aluminum alloy products, the technological parameters of the process must ensure the specified accuracy and processing performance. This guarantees the maximum heat exchange properties of the surfaces of the processed parts, critical for applications where efficient thermal management is essential. Enhancing these properties can significantly impact the operational efficiency of systems in aerospace, automotive, and electronics industries. Articles on the interrelationship of cutting modes and technological and energy parameters of the milling process of prismatic channels in aluminum alloys is an actual task. Its practical implementation will guarantee the improvement of various facilities for transferring and releasing thermal energy. This research could lead to advancements in heat sink design and more effective cooling strategies in high-performance engineering applications, where optimal heat dissipation is vital for maintaining system stability and prolonging lifespan.